Identifikasi Golongan Darah Anjing Kampung dengan Antibodi Monoklonal - Rosita Supriadi, Helny; Washio, Masaji; -, Gunanti; Rita Ekastuti, Damiana; Agungpriyono, Srihadi (Jurnal Veteriner; Vol 8 No 4 (2007), 2007)
A study was carried out to identify the blood groups of dogs and to determine their distribution among dog population as well as their possible relationship with hair color, sexes and location. Fifty dogs were used in this study and they were originated from Jakarta, Bekasi and Bogor, Indonesia. The blood groups of dogs were determined by monoclonal antibodies and a positive reaction was characterized by the presence of agglutination as a result of antigen-antibody reaction. Three blood groups, 1.1B (44.0%), 1.2B (42.0%) and 1(-)B (14.0%) were detected among the 50 dogs examined. No significant relationship between certain the blood groups and the hair color, sexes and their origin were detected in this study.
Keywords: local breed dogs, blood type, monoclonal antibody